Zero-, one-, two- and three-dimensional coordination polymers based on tetracarboxylic acid: Syntheses, structures, magnetic and luminescent properties. (November 2015) - Yang, Li-rong; Liu, Liu; Lian, Chen; Liu, Meng-yan; Xu, Zhen-huan; Wang, Li-Ce; Guo, Xu; Long, Yin-shuang
Abstract: A series of coordination polymers, namely, [Co(H2 ttac)(phen)2 ]4H2 On (1 ), [Zn(H2 ttac)(phen)2 ]4H2 On (2 ), [Cu(H2 ttac)(phen)]n (3 ), [Zn2 (ttac)(DMZ)H2 O]n (4 ), and [Cd(ttac)(phen)H2 O]n (5 )(H4 ttac = 4, 5-di(3'-carboxylphenyl)-phthalic acid, phen = 1, 10-phenanthroline, DMZ = Dimidazole) have been prepared under hydrothermal conditions and characterized by elemental analysis, IR spectroscopy, and single crystal X-ray diffraction. Structural analysis reveals that the as-synthesized coordination polymers have different structures, ranging from zero-(1 and2 ), one-(3 ), two-(4 ) to three-(5 ) dimensions, which are mainly due to the different metal ions, the degree of deprotonation and coordination modes of the H4 ttac ligands. It is worth mentioning that, based on the diversified π – π stacking and/or C–H··· π interactions between H4 ttac ligands and/or nitrogen-containing auxiliary ligands, 1 –4 are assembled form low-dimensional structures into three-dimensional (3D) frameworks. Especially, Jahn-Teller effect occurs in3 and its magnetic study confirms that it presents antiferromagnetic coupling through the (O2 C-Ar-Ar-CO2 )2 bridges. Significantly, luminescent emission of3 displays selective recognition towards L-Arginin. Thermogravimetric (TG) analyses of the coordination polymers have also been investigated. Graphical abstract: A series of coordination polymers, namely, [Co(H2 ttac)(phen)2 ]4H2 On (1 ), [Zn(H2 ttac)(phen)2 ]4H2 On (2 ), [Cu(H2 ttac)(phen)]n (3 ), [Zn2 (ttac)(DMZ)H2 O]n (4 ), and [Cd(ttac)(phen)H2 O]n (5 )(H4 ttac = 4, 5-di(3'-carboxylphenyl)-phthalic acid, phen = 1, 10-phenanthroline, DMZ = Dimidazole) have been prepared under hydrothermal conditions and characterized. Structural analysis indicates that coordination polymers1 –4 are assembled from low-dimensional structures into three-dimensional frameworks. The luminescent emission of3 displays selective recognition towards L-Arginin. Highlights: A series of coordination polymers have been prepared. The coordination polymers are assembled form low-dimensional structures into three-dimensional frameworks through intermolecular forces. Coordination polymer 3 displays selective recognition towards L-Arginin.